2016
DOI: 10.1002/jcla.22069
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference intervals for serum thyroid-stimulating hormone, free and total thyroxine, and free and total triiodothyronine for the Beckman Coulter DxI-800 analyzers by indirect method using data obtained from Chinese population in Zhejiang

Abstract: Background In order to establish suitable reference intervals of thyroid‐stimulating hormone (TSH), free (unbound) T4 (FT4), free triiodothyronine (FT3), total thyroxine (T4), and total triiodothyronine (T3) for the patients collected in Zhejiang, China, an indirect method was developed using the data from the people presented for routine health check‐up. Methods Fifteen thousand nine hundred and fifty‐six person's results were reviewed. Box‐Cox or Case Rank was used to transform the data to normal distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
2
14
1
1
Order By: Relevance
“…However, various clinical laboratories use the RIs proposed by the manufacturer of these tests, which are mainly based on data from non-Chinese populations. In addition to ethnicity, the RIs for thyroid-associated hormones are influenced by several other factors, including the time of day, age, sex, iodine levels, and inter-assay differences [ 6 8 ]. Considering these facts, each laboratory should establish population-based and method-specific RIs, as recommended by the International Federation of Clinical Chemistry, Clinical & Laboratory Standards Institute (CLSI), and American Thyroid Association [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, various clinical laboratories use the RIs proposed by the manufacturer of these tests, which are mainly based on data from non-Chinese populations. In addition to ethnicity, the RIs for thyroid-associated hormones are influenced by several other factors, including the time of day, age, sex, iodine levels, and inter-assay differences [ 6 8 ]. Considering these facts, each laboratory should establish population-based and method-specific RIs, as recommended by the International Federation of Clinical Chemistry, Clinical & Laboratory Standards Institute (CLSI), and American Thyroid Association [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al suggested that the standard parametric or non‐parametric statistical approach can be used in the indirect method for RIs when the data were collected at a community screening project or similar. In fact, the parametric approach has been used in the analysis of data from NHANES, and the non‐parametric approach has been used in a Chinese and a Turkish study, respectively . Of course, when the standard parametric approach is used, this will involve data transformation if the data are non‐normal or asymmetric distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Parametric or non-parametric percentile statistical approach as described in the CLSI guidelines EP-A3 guidelines can be used to calculate RIs in indirect method. 21,24,25,33 For parametric approach, the 95% RIs (double-sided) was defined mean ± 1.96 SD; for nonparametric approach, the values of the 2.5th and 97.5th percentile were used as lower and upper limits of RIs following the guideline EP28-A3, 23 respectively. Meanwhile, the 90% confidence intervals (CI) for lower and upper limits were also calculated.…”
Section: Determination Of Rismentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzers and analytes: Three Beckman Coulter DxI‐800 analyzers 11 (Beckman Coulter, S. Kraemer Boulevard) in Zhejiang Provincial People's Hospital in China were selected in our research and were named ZrmDxi_1, ZrmDxi_2, and ZrmDxi_3, respectively. Five analytes including thyrotropin (TSH), total thyroxine (TT4), total triiodothyronine (TT3), free thyroxine (FT4), and free triiodothyronine (FT3) were measured in the three analyzers every day from January 1st to September 20th in 2019.…”
Section: Methodsmentioning
confidence: 99%